Distribution and phylogenetic inference within the flightless spring katydids (Tettigoniidae: Brinckiella Chopard, 1955) in the Greater Cape Floristic Region - Guta, Ricardo José (Department of Biological Sciences, 2023)
The genus Brinckiella is an endemic group from the Greater Cape Floristic region (GCFR) with several undescribed species. Some of them are of conservation concern, categorized by IUCN as Endangered (EN) and Vulnerable (VU) due to their restricted distribution caused by livestock overgrazing, agriculture, and urbanization. However, data are still missing to fully assess their distribution pattern and conservation status. Moreover, although the phylogeny of katydids was recently inferred, Brinckiella was not included in that analysis. Thus, its closest relatives and evolutionary history are still unknown. This study aimed to investigate the distribution and phylogenetic inference within the genus Brinckiella, map the distribution of its species, delimit the species through taxonomy and genetics, and elucidate the phylogenetic relationship and divergence time within the genus. Specimens were collected by hand and sweep netting. Phylogenetic inference was done using the COI gene and analysed under Maximum likelihood and Bayesian inference. This study identified 13 morphospecies of Brinckiella, of which five are new, undescribed species. The genus is currently distributed in 27 vegetation types in three biomes, and apart from the Fynbos and Succulent Karoo biomes, the genus also occurs in the Azonal vegetation biome. Fynbos had the highest number of species of Brinckiella, which is likely related to the vast diversity of plant that they are associated with and probably feed on. In the Succulent Karoo the distribution of Brinckiella might be associated with seasonal plants that occur in the spring and at the beginning of summer. The genus may be monophyletic, and it split from the common ancestor shared with Holochlora fruhstorferi Carl, 1914 about 14.2 Mya, and it split again from the common ancestor shared with Isophya major Brunner von Wattenwyl, 1878, Phaneroptera gracilis Burmeister, 1838 and Kuwayamaea chinensis (Brunner von Wattenwyl, 1878) at 10.16 Mya and diverged in the late Miocene around 8.79 Mya, producing two main clades (A and B). Clade A diverged 7.85 Mya and is composed by two closely related species: B. aptera and B. mauerbergerorum, while Clade B diverged 7.24 Mya and gave rise to two lineages (L1 and L2). Brinckiella wilsoni constitutes L1, and L2 split later in the early Pliocene around 4.74 Mya, and is represented by two sister species, B. arboricola and B. sp. n. 5.